Tenancy Agreement: Can Tenant Declare that the Agreement is Void due to Movement Control Order? - MUHAMMAD ASYRAF AZNI; Suria Fadhillah Md Pauzi (Faculty of Law, Universitas Jenderal Soedirman, 2021)
The government of Malaysia has declared Movement Control Order (MCO) for the whole Malaysia in order to flatten the curve of Covid-19 infection. Universities, such as UiTM, consequently has been ordered by the government to close its campuses and as such students who are renting a house are wondering whether they can terminate the tenancy agreement which they have entered into. The paper analyses the legal position of doctrine of frustration and force majeure in this context. The analysis is done based on the cases and/or legal provisions from various jurisdiction such Malaysia, Singapore, and the United Kingdom. This paper finds that force majeure clause is most likely cannot be used to terminate the agreement because this clause is usually not included in the terms of the agreement. Doctrine of frustration on the other hand might be use as a ground to terminate the agreement. However, the court will apply the doctrine of frustration in a very careful manner so as to respect the sanctity of the agreement. In conclusion, whether or not tenancy agreement can be terminated due to MCO, it will all depends on the terms of each tenancy agreement.Keywords: contract; Covid-19; force majeure; frustration; MCO